1988
DOI: 10.1029/jb093ib07p07834
|View full text |Cite
|
Sign up to set email alerts
|

Determination of in situ stress orientation from borehole guided waves

Abstract: We have analyzed the horizontal particle motion of borehole guided waves from three‐component vertical seismic profile data recorded from three experiments. The polarization directions of the guided waves are consistent with the direction of horizontal principal stress determined independently. We suggest that stress‐induced velocity anisotropy in the rock adjacent to the borehole appears to cause antisymmetric flexural guided modes to be polarized in the direction of the maximum horizontal principal stress. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…If we assume that the tube waves correspond t o a symmetrical radial mode, the horizontal projection of the tube-wave polarization should ideally always be radial on the well. In order to discover if this was the case in our data or whether the tube waves showed polarization anomalies in accordance with the observations of Barton and Zoback (1988), two polarization angles were studied (Fig. 11).…”
Section: T U B E -W a V E R E F L E C I ' I O N A N A I Y S I Ssupporting
confidence: 73%
See 1 more Smart Citation
“…If we assume that the tube waves correspond t o a symmetrical radial mode, the horizontal projection of the tube-wave polarization should ideally always be radial on the well. In order to discover if this was the case in our data or whether the tube waves showed polarization anomalies in accordance with the observations of Barton and Zoback (1988), two polarization angles were studied (Fig. 11).…”
Section: T U B E -W a V E R E F L E C I ' I O N A N A I Y S I Ssupporting
confidence: 73%
“…The tube-wave velocity dispersion and particle motions can he used to test for geophone coupling and for lithology identification (Cheng and Toksöz 1982), and tube waves have been reported to be very sensitive to Open fractures and high permeability zones (White 1983). In addition, recent observations of the tube-wave particle motions have suggested that the horizontal particle motion is polarized in the direction of a local principal axis of stress (Barton and Zoback 1988).…”
Section: Introductionmentioning
confidence: 99%
“…That such planes do, indeed, exist is suggested by the close agreement between the directions of the maximum horizontal principal stress in this well [ Moos et al ., 1988; Plumb , 1988] and the P‐axis from a composite focal mechanism for a shallow (1.3–1.9 km deep) swarm of reverse‐faulting earthquakes that occurred within 0.5 km of the well [ Mrotek et al ., 1988; Woodward‐Clyde Consultants , 1988]. High‐stress normal faulting is suggested by recent in‐situ stress measurements in four different wells at depths of 0.3–1.7 km beneath Yucca Mountain, Nevada [ Stock et al ., 1985, 1986; Stock and Healy , 1988a] and by in‐situ stress measurements and borehole breakout analyses at depths of 3–4.5 km beneath Fenton Hill, New Mexico [ Barton et al ., 1988; see also earthquake fault‐plane determinations by Fehler , 1989].…”
Section: State Of Stress On Active Faultsmentioning
confidence: 99%
“…Recent observations of particle motion in vertical seismic profile (VSP) surveys [Barton and Zoback, 1988] (hereinafter referred to as Barton and Zoback) suggest the existence of borehole waves for which the horizontal particle motion at the borehole wall is polarized in a specific azimuthal direction. These reported low-frequency arrivals superficially resemble "tube waves," which are often excited in VSP surveys.…”
Section: Introductionmentioning
confidence: 99%